MODERN DIGITAL IMAGINARIES: FACEBOOK AS A SOURCE OF INDEPENDENT NARRATIVES IN COLOMBIA - Velez, Natalia (AoIR Selected Papers of Internet Research, 2015)
As much as networked digital media has proven to be a powerful tool for coordinating and consolidating political action, the study of this issue in the context of Latin America requires an additional understanding of Latin American countries’ political and economic landscapes. In this paper, I analyze the activist group “Voces contra las FARC”’s use of Facebook during a period of acute political debate in comparison to that of the two local newspapers with the highest circulation rates, El Tiempo and El Espectador. This article expands the existing theories about the power of social media in countries with corrupted political sceneries and provides insights that could be used for comparative analysis between Latin American countries in hopes of characterizing the networked environment in the region.